“Walls of Words”: Paperscape in Charles Dickens’s Novels - Céline PREST (E-REA)
The walls of Dickens’s city are covered in posters, bills, signs and inscriptions, resulting in the disappearance of those very walls behind the accumulation of messages. Simultaneously, these words go beyond the space allotted to them, erecting walls of words in the public space, constantly modifying the cityscape. This new urban landscape became possible with the lifting of paper taxes and the technological evolutions of the nineteenth century. This change initiates a new urban experience: walls now directly address the city dweller who is perpetually asked to decipher disparate messages. The reader follows David Copperfield, Pip and Oliver Twist as they read the writing on the wall, sometimes their only guide in the city. This writing transforms London into a gigantic map on which the characters move. This textual world is reproduced in the pages of the novels and influences the reader’s act of reading, in that he is now asked to adopt a non-linear, non-sequential—and urban—mode of reading. Over this Dickensian paperscape looms the threat of illegibility. This overabundance of words and paper has developed into its own demise: if walls are covered in words, words can in turn acquire the solidity and opacity of walls. Paper appears less the medium for words than the shroud of meaning.Following the lead of Asa Briggs and his book Victorian Things which analyses the commodity culture of Victorian England, this article aims at showing the ambivalence of the Dickensian text towards the material presence of the written sign: while paper in its multiple forms is invested with a negative—even evil—power, it also proves to be the very organising principle of the narrative and the cityscape. Our corpus will consist of a selection of novels—Oliver Twist, David Copperfield, Bleak House, Little Dorrit and Our Mutual Friend—and five essays with “Bill-Sticking,” “Our Watering Place,” “Out of Town,” “Travelling Abroad” and “Some Recollections of Mortality,” in an effort to show the author’s concern for the materiality of the written sign from the very beginning of his career until the very end.